Characterization and evaluation of ber genotypes in hot arid regions of Tamil Nadu (Indian Journal of Arid Horticulture, 2013)
Ber (Ziziphus mauritiana Lamk.) is an economically important tropical fruit tree, which is grown  all over the drier parts of the Indian subcontinent, Africa  and northern Australia for its fresh fruits. It is one of the  suitable trees to grow in dry regions, because it can  withstand long periods of drought. Ber (Chinese date,  Chinese Fig or bore) also known as poor man's fruit is most  widely cultivated in Punjab, Haryana, Rajasthan, Uttar  Pradesh, Madhya Pradesh, Bihar, Gujarat, Maharashtra etc.  Liu and Cheng (1995) reported that Indo-Malaysia region is  the centre of both evolution and distribution of the genus  Zizyphus. In India, a number of ber cultivars have been  developed largely by the growers through selection in  different regions. Maximum variability of ber is observed  in Rajasthan, Gujarat, Haryana, Punjab and Madhya  Pradesh and Uttar Pradesh. In Gujarat, Mehsana, Anand,  Panchmahal, Patan and Sabarkatha districts are having rich  diversity of ber(Shukla et al., 2003).
Keywords: Aruppukottai; Rajasthan; Uttar Pradesh